Evaluation of toll-like receptors 2 and 4 polymorphism and intestinal microbiota in children with food allergies - Kilic, Mehmet; Beyazit, Elif; Onalan, Ebru Etem; Kaymaz, Tugce; Taskin, Erdal (Turkish J Pediatrics, 2023)
Background. Mutual regulation between immune system and gut microbiota is achieved through several mechanisms including the engagement of toll-like receptors (TLRs) which is expressed on numerous cell types. In this study we aimed to explore the association between food allergies and TLR gene polymorphisms in association with gut microbiota.Methods. Toll-like receptors polymorphism frequencies and some bacteria in the gut microbiota in 130 infants aged 1-24 months with egg and/or milk allergy in a prospective cohort were compared with 110 non-food allergic controls. Four candidate polymorphisms (TLR2 rs1898830/rs5743708 and TLR4 rs4986790/rs4986791) were genotyped by allelic discrimination polymerase chain rection (PCR) method. Gut microbiota analysis was achieved by using high-throughput sequencing.Results. The TLR4 rs4986790 (Asp299Gly) single nucleotide polymorphism (SNP) major/minor allele frequency was 0.788/0.212 in food allergy patients and 0.719/0.280 in controls (p=0.017). There was a statistically significant difference between groups in terms of genotype frequencies (AA, AG, GG). Gut microbiota analysis revealed increased Firmicutes phylum in stool of the patients with food allergy. Except for TLR4 rs4986791 (Thr399lle) allele, the other TLR polymorphisms were not associated with food allergies in children. When the bacteria in the intestinal microbiota and TLR2 and TLR4 gene polymorphisms were compared; we determined a statistically significant increase in Bifidobacterium concentration in the intestinal microbiota in TLR4 rs4986791 CT heterozygous genotype (p=0.004).Conclusions. This study demonstrated a partial role of TLR4 gene polymorphism and gut microbiota in the development of food allergies. Future work in this area will be required to clarify the roles of different microbial strains that modulate gut microbiota composition and function in conjunction with TLR transcription pathways.
Keywords: food allergy; Toll-like receptor 2; Toll-like receptor 4; genetic polymorphism; gut microbiota; children